2013
DOI: 10.1002/elps.201300100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of selected parasites from people with histories of gastrointestinal disorders using a mutation scanning‐coupled approach

Abstract: A SSCP analysis and targeted sequencing approach was used for the genetic characterization of some major pathogens from a cohort of 227 people with histories of gastrointestinal disorders. Genomic DNAs from fecal samples were subjected to PCR-amplification of regions in the glycoprotein (gp60) or triose phosphate isomerase (tpi) gene, or the second internal transcribed spacer of nuclear ribosomal DNA (ITS-2). Cryptosporidium, Giardia, and strongylid nematodes were detected in 94, 132 and 12 samples. Cryptospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 80 publications
1
36
0
1
Order By: Relevance
“…cuniculus , a novel Cryptosporidium species most closely related to C . wrairi and the Cryptosporidium mink genotype have been reported [24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42]. The aim of the present study was to use molecular tools to identify the Cryptosporidium sp.…”
Section: Introductionmentioning
confidence: 99%
“…cuniculus , a novel Cryptosporidium species most closely related to C . wrairi and the Cryptosporidium mink genotype have been reported [24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42]. The aim of the present study was to use molecular tools to identify the Cryptosporidium sp.…”
Section: Introductionmentioning
confidence: 99%
“…However, no clinical information was available. 13 In our case, although the laboratory results showed that hemoglobin was slightly below the normal limit, it may not have been caused by A. ceylanicum infection, because only a single worm was observed and recovered during endoscopy.…”
mentioning
confidence: 47%
“…Although gene microarray is rapid and specific, probe synthesis cycle is longer, and the cost is expensive (Wang et al 2004). Single-strand conformation polymorphism (SSCP) has advantage of lower cost, except complex operation and bad specificity (Koehler et al 2013). Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) is low requirement for equipment, but with ethidium bromide, and manual operation for every step.…”
Section: Discussionmentioning
confidence: 99%